2017
DOI: 10.1038/nsmb.3483
|View full text |Cite|
|
Sign up to set email alerts
|

A structural model for microtubule minus-end recognition and protection by CAMSAP proteins

Abstract: CAMSAP and Patronin family members regulate microtubule minus-end stability and localization and thus organize non-centrosomal microtubule networks, which are essential for cell division, polarization and differentiation. Here, we show that the C-terminal CKK domain of CAMSAPs is widely present among eukaryotes and autonomously recognizes microtubule minus ends. Through a combination of structural approaches, we uncover how mammalian CKK binds between two tubulin dimers at the inter-protofilament interface on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
151
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(167 citation statements)
references
References 75 publications
(91 reference statements)
15
151
1
Order By: Relevance
“…Can CKK binding to different MT protofilament architectures shed further light on the mechanism of minus end recognition? Intriguingly, we also previously identified CKKs in the amoeboflagellate N. gruberi and the potato blight fungus P. infestans that had lost the binding preference for MT minus ends that was proposed to be present in CKK domains from the last eukaryotic common ancestor 2 . Can a comparison of CKK domains with and without minus-end binding specificity also provide insight into MT minus-end recognition?…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Can CKK binding to different MT protofilament architectures shed further light on the mechanism of minus end recognition? Intriguingly, we also previously identified CKKs in the amoeboflagellate N. gruberi and the potato blight fungus P. infestans that had lost the binding preference for MT minus ends that was proposed to be present in CKK domains from the last eukaryotic common ancestor 2 . Can a comparison of CKK domains with and without minus-end binding specificity also provide insight into MT minus-end recognition?…”
Section: Introductionmentioning
confidence: 90%
“…Strep-GFP-tagged human CAMSAP1 CKK (residues 1474-C) and Naegleria gruberi CKK (residues 612-C, reference sequence XM_002675733.1) were prepared as described previously (Atherton et al, 2017). Briefly, both proteins were expressed in HEK293T cells using a modified pTT5 expression vector (Addgene no.…”
Section: Protein Expression and Purification For Tirf Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…How Patronin functions to assemble MTs at the ncMTOC remains incompletely understood. Patronin/CAMSAP stabilizes MT minus-ends and antagonizes the activity of Kinesin-13 family depolymerases (Goodwin and Vale, 2010;Hendershott and Vale, 2014;Atherton et al, 2017). However, this antagonism does not prevail at the fat body ncMTOC because Kinesin-13 (Klp10A) knockdown, or other MT depolymerases Klp59C or Klp59D did not suppress the reduced circumferential MTs in Patronin knockdown cells ( Figure 17E, F).…”
Section: Patronin Controls Circumferential Mt Assembly At the Ncmtocmentioning
confidence: 97%
“…The XMAP215/Msps/Stu2/ Dis1/Alp14/ZYG-9/ch-TOG/MOR1 is an ancient family of MT polymerases that was recently identified as a new in vivo MT nucleator at centrosomes and spindle pole bodies through its association with g-tubulin (Flor-Parra et al, 2018;Gunzelmann et al, 2018;Thawani et al, 2018); a role for the MT polymerase at nucleating MTs at ncMTOCs has not been reported. Additionally, the recently identified CAMSAP/Patronin family of MT minus-end proteins protects MT minusends from Kinesin-13 family depolymerases (Goodwin and Vale, 2010;Hendershott and Vale, 2014;Atherton et al, 2017). CAMSAP/Patronin has emerged as a critical player at ncMTOCs via unclear mechanisms.…”
Section: Introductionmentioning
confidence: 99%